Effects of Aqueous Ginger Extract on Some Hematology Parameters, Serum Iron, Ferritin, and Total Iron Binding Capacity in Male Mice (Mus musculus L.) - Almajeed, Mustafa Abd; Ibrahim, Nawal Khalil (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Ginger is a common spice with wide range of medicinal properties, the extract have wide chemical substances play important role for many effects in humans and animals. Aim: The present study aimed to evaluate the effect of ginger on some hematological parameters as well as on serum iron, ferritin and total iron binding capacity. Subjects and methods: Thirty mice adult male be split into three groups, two treated groups and one control group (each group contains ten mice). The experimental groups were injected by intraperiton (IP) with 0.1 ml in every dose, (2 mg and 4 mg/mice) of Zingibar officinale extract was injected in treated groups, also a stander group received the distill water with the same dose. Results: PCV significantly rises in both dose, also Hb, RBC, MCV and MCHC appeared significant increase only in high dose. While MCH clarified not significant affect in two doses. TIBC not reach to significant differences in groups treated with two potion, whereas, rises serum iron and ferritin significantly appeared in high dose only compared with group in control at (p<0.01). Conclusions: The ginger safe and help in iron absorption and can be beneficial as a promising therapy to prevent and treat iron deficiency anemia.